2006
DOI: 10.1534/genetics.106.063016
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Drosophila Translin and Trax

Abstract: The vertebrate RNA and ssDNA-binding protein Translin has been suggested to function in a variety of cellular processes, including DNA damage response, RNA transport, and translational control. The Translin-associated factor X (Trax) interacts with Translin, and Trax protein stability depends on the presence of Translin. To determine the function of the Drosophila Translin and Trax, we generated a translin null mutant and isolated a trax nonsense mutation. translin and trax single and double mutants are viable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…Quantification of whole-brain fluorescence confirmed that TRSN protein is increased in response to starvation (Figure 3C-D). In agreement with previous findings, TRSN signal is below detection in trsn null mutants and dramatically reduced in nSyb -GAL4> trsn -IR flies confirming the antibody specifically labels TRSN (data not shown and [13]). Counterstaining with the neuronal marker Embryonic Lethal Abnormal Vision (ELAV) revealed that TRSN and ELAV are expressed in all neurons during the fed and starved states (Figure 3E), suggesting the observed changes in protein levels are not due to altered protein localization.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Quantification of whole-brain fluorescence confirmed that TRSN protein is increased in response to starvation (Figure 3C-D). In agreement with previous findings, TRSN signal is below detection in trsn null mutants and dramatically reduced in nSyb -GAL4> trsn -IR flies confirming the antibody specifically labels TRSN (data not shown and [13]). Counterstaining with the neuronal marker Embryonic Lethal Abnormal Vision (ELAV) revealed that TRSN and ELAV are expressed in all neurons during the fed and starved states (Figure 3E), suggesting the observed changes in protein levels are not due to altered protein localization.…”
Section: Resultssupporting
confidence: 93%
“…Both male and female flies with a P-element insertion in the trsn locus ( trsn EP ) or the excision allele ( trsn null ) are viable [13] and exhibit reduced sleep suppression during starvation (Figure 1F-H and S1C-D), phenocopying flies with neuron-specific RNAi knockdown. The waking activity of trsn null flies phenocopies RNAi knockdown flies under fed conditions, while starvation-induced hyperactivity is blunted or absent in trsn mutants (Figure S1E).…”
Section: Resultsmentioning
confidence: 99%
“…Tsn and Trax are highly conserved and coexist in many eukaryotes (36), including fission yeast, Drosophila melanogaster ( Drosophila ) and animals. They are involved in many important biological processes, such as normal cell growth, genome stability maintenance, neuronal development, spermatogenesis, RNA trafficking and RNA metabolism (711).…”
Section: Introductionmentioning
confidence: 99%
“…They were identified by mass spectrometry as the evolutionarily conserved Translin/TB-RBP and Translin-associated factor X (Trax). Translin is a single-stranded DNA/RNA-binding protein that co-purifies with siRNA after UV crosslinking (10, 11), whereas Trax has sequence similarity to and interacts with Translin (12). Consistently, recombinant C3PO complex, but not Translin, greatly enhanced the RISC activity of recombinant Dcr-2/R2D2/Ago2 (Fig.…”
mentioning
confidence: 99%
“…Western blotting revealed that Translin and Trax were both missing in translin ( trsn ) mutant fly lysate (Fig. 2A) (11), suggesting that Trax is unstable without Translin. By contrast, the core RNAi components, i.e.…”
mentioning
confidence: 99%